A 4, 5-quinolimide-based fluorescent sensor for the turn-on detection of Cd2+ with live-cell imaging. Issue 10 (21st February 2017) - Zhang, Yu; Guo, Xiangfeng; Zheng, Mengmeng; Yang, Rui; Yang, Hongming; Jia, Lihua; Yang, Mengmeng
Abstract : The first 4, 5-quinolimide sensor, BNA, bearing the amide-DPA receptor, was reported for sensing Cd 2+ with live-cell imaging. Abstract : A 4, 5-quinolimide derivative, BNA, bearing the amide-DPA receptor, was synthesized as a turn-on fluorescent sensor for Cd 2+ . Under physiological conditions, BNA could distinguish Cd 2+ from Zn 2+, showing turn-on fluorescence behaviour and an increased fluorescence lifetime.BNA and Cd 2+ formed a 1 : 1 stoichiometric complex, and the detection limit was measured to be as low as 11 nM. Furthermore, BNA was utilized for fluorescence imaging of Cd 2+ in live cells. To the best of our knowledge, it is the first 4, 5-quinolimide-based sensor for the detection of metal ions.